2019
DOI: 10.1016/j.molcel.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

System-wide Profiling of RNA-Binding Proteins Uncovers Key Regulators of Virus Infection

Abstract: Summary The compendium of RNA-binding proteins (RBPs) has been greatly expanded by the development of RNA-interactome capture (RIC). However, it remained unknown if the complement of RBPs changes in response to environmental perturbations and whether these rearrangements are important. To answer these questions, we developed “comparative RIC” and applied it to cells challenged with an RNA virus called sindbis (SINV). Over 200 RBPs display differential interaction with RNA upon SINV infection. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
209
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(224 citation statements)
references
References 75 publications
11
209
0
Order By: Relevance
“…Further samples were prepared from stable and inducible HeLa cells expressing mov10-YFP [30] to label p-bodies. HeLa cells were induced to produce mov10-YFP by supplementation of the medium with 1 mg/ml doxycycline and then infected with sindbis virus (SINV-mCherry, see below [31]) and then incubated with MitoTracker Deep Red (Thermo Fisher) at 125 nM for 30 minutes before being plunge frozen as above for imaging.…”
Section: Cellular Sample Preparationmentioning
confidence: 99%
“…Further samples were prepared from stable and inducible HeLa cells expressing mov10-YFP [30] to label p-bodies. HeLa cells were induced to produce mov10-YFP by supplementation of the medium with 1 mg/ml doxycycline and then infected with sindbis virus (SINV-mCherry, see below [31]) and then incubated with MitoTracker Deep Red (Thermo Fisher) at 125 nM for 30 minutes before being plunge frozen as above for imaging.…”
Section: Cellular Sample Preparationmentioning
confidence: 99%
“…As a result, peptide intensity ratios cannot be calculated for all proteins because of the low complexity of the -4SU samples. For these proteins one can use a semiquantitative approach that assumes that peptides with zero intensity values are below the detection threshold 3,24 (Figure 3). After determining the candidate "VIR-CLASP RBPs", comparisons can be made between the conditions, timepoints, viruses, or cell lines tested.…”
Section: (See Supplementarymentioning
confidence: 99%
“…Previous studies already showed that genomes of the Dengue viruses interact with multiple human proteins during the infection and that the protein binding can enhance or inhibit the virulence 31 . Furthermore, RNA binding proteins tend to exhibit an altered activity during viral infection, in some cases due to the presence of highly abundant viral RNA, which can compete for the interaction with cellular RNA 32 . To study the relationship between human proteins and the viral RNA structures, we selected binding motifs from RNA Bind-n-Seq (RBNS) data of 78 human RNA-binding proteins 23 , and searched the complete viral genomes for these motifs (Materials and Methods: Protein-RNA interactions).…”
Section: Interaction Between Viral Genomes and Human Host Proteins Camentioning
confidence: 99%